Operative GABAergic inhibition in hippocampal CA1 pyramidal neurons in experimental epilepsy - Esclapez, M. (The National Academy of Sciences of the USA, 1997)
Patch–clamp recordings of CA1 interneurons and pyramidal cells were performed in hippocampal slices from kainate- or pilocarpine-treated rat models of temporal lobe epilepsy. We report that γ-aminobutyric acid (GABA)ergic inhibition in pyramidal neurons is still functional in temporal lobe epilepsy because: (i) the frequency of spontaneous GABAergic currents is similar to that of control and (ii) focal electrical stimulation of interneurons evokes a hyperpolarization that prevents the generation of action potentials. In paired recordings of interneurons and pyramidal cells, synchronous interictal activities were recorded. Furthermore, large network-driven GABAergic inhibitory postsynaptic currents were present in pyramidal cells during interictal discharges. The duration of these interictal discharges was increased by the GABA type A antagonist bicuculline. We conclude that GABAergic inhibition is still present and functional in these experimental models and that the principal defect of inhibition does not lie in a complete disconnection of GABAergic interneurons from their glutamatergic inputs.